Deep Eutectic Solvents (DESs) in Waste Reduction, By-Product Valorization, and Advancing the Circular Economy - Maria Bairaktari (Sustainable Chemical Engineering, 2025)
The growing demand for sustainable solutions in industrial processes has prompted the exploration of alternative solvents that can reduce environmental impact. Deep Eutectic Solvents (DESs), characterized by their low toxicity, recyclability, and versatility, have emerged as promising candidates for waste reduction, by-product valorization, and the advancement of the circular economy. This mini-review highlights the main applications ofDESs in various waste management strategies. Firstly, it examines DES as a green, non-toxic, and alternative solvent to conventional solvents, offering a safer and more sustainable option for industrial processes. Secondly, it examines their role in reducing food and agro-industrial waste by extracting valuable bioactive compounds from waste streams and industrial by-products. Thirdly, it discusses the recovery of valuable metals from electronic waste (e-waste), emphasizing the efficiency of DESs in metal extraction while minimizing environmental harm. Finally, it addresses the use of DESs in catalyst cleaning and regeneration, showcasing their contribution to reducing waste in industrial catalytic processes. Overall, this review provides a comprehensive and up-to-date analysis of DESs as pretreatment agents, extraction solvents, catalysts, and material recovery media, compiling the most recent advances in agro-industrial waste valorization, precious metal recovery, and catalyst regeneration. It offers comparative insights into their performance against conventional solvent-based methods and highlights emerging challenges and opportunities for large-scale implementation, emphasizing their potential to advance waste reduction and support a circular economy.